Estimated Pollution Reduction from Wind Farms in Oklahoma and Associated Economic and Human Health Benefits - Greene, J. Scott; Morrissey, Mark (Journal of Renewable Energy, 2013)
Over the past few decades, there has been a recognition of the growing need for different forms of energy outside of fossil fuels. Since the latter half of the twentieth century individuals, corporations, and governments have become increasingly aware of the effects of the emissions of carbon and other harmful pollutants on the environment. With this greater concern has come increasing activity to combat these harmful emissions by using alternative fuel sources to power homes, businesses, and cities. As can be seen from recent trends in their installed capacity, it is clear that renewable energy resources will continue to be more commonly used in the future. As renewable energy increases, a decrease in a range of harmful pollutants from the energy sector will also occur. This paper provides a case study to estimate the potential environmental and health benefits of an increased shift from fossil fuels to renewable fuels for electrical production in Oklahoma. Results illustrate and quantify the specific reduction that wind energy can and will have on air quality, as well as provide a quantification of the associated potential health benefits.